Integrasi DNA Barcode COI dan ITS Mengungkap Keanekaragaman Kriptik serta Batasan Spesies dalam Genus Padina - Yessy Yessy; Fenti Fatmawati; Malikhatun Ni’mah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the molecular characteristics and phylogenetic relationships of the genus Padina using COI and ITS markers, as well as to evaluate the presence of cryptic diversity and species delimitation based on molecular phylogenetic approaches. Phylogenetic analysis was conducted on 66 COI sequences and 25 ITS sequences obtained from GenBank. Sequence alignment was performed using the ClustalW algorithm, while phylogenetic tree reconstruction was carried out using Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods with MEGA 12 software. Pairwise genetic distances were calculated using the Maximum Composite Likelihood model, and bootstrap analysis was performed with 1,000 replicates. The results showed that the NJ and ML tree topologies had high consistency, with bootstrap values of 70–100% at the main nodes. The analysis successfully confirmed the monophyly of P. mexicana, P. crispata, P. durvillei, P. antillarum, P. bergesenii, P. haitiensis, P. boryana, and P. minor. In contrast, Padina gymnospora showed a paraphyletic condition, indicating the possibility of a species complex. The COI marker revealed a clear barcoding gap, with intraspecific genetic distances (0.000–0.081) lower than interspecific genetic distances (0.091–0.165). Unidentified specimens showed genetic distances of 0.064–0.103 from P. durvillei and 0.053–0.215 from P. gymnospora, indicating significant genetic differentiation. The ITS marker showed 94.8% variable sites and 82.9% parsimony-informative sites, while COI had 43.2% variable sites and 34.9% parsimony-informative sites. Therefore, the combination of COI and ITS markers was proven effective in reconstructing phylogenetic relationships, revealing cryptic diversity, and supporting species delimitation in the genus Padina, which has high morphological plasticity. Keywords: COI, Cryptic Diversity, ITS, Molecular Phylogenetics, Species Delimitation